A Numerical Analysis of Recycled Aluminium Alloys Reinforced with Alumina Oxide Subjected to High Velocity Impact - Muhammad Rodhi, Adam Syauqi; Mohd Nor, Mohd Khir; Maat, Norzarina; Abdul Samad, Mohd Syazwan (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Developing superior recycled aluminium as a replacement for primary sources, a variety investigation must first be done to determine the material's mechanical behaviour. Aluminium oxide, often known as α-Al2O3, is a chemical compound made up of aluminium and oxygen with the formula α-Al2O3. A previous experimental test on the deformation behaviour and fracture mode of recycled aluminium alloy AA6061 reinforced alumina oxide during Taylor impact tests at 191ms , 209ms , 220ms and 231ms . In this research project, the deformation behaviour and fracture mode are investigated numerically with implementing Johnson-Cook material model. The parameters are calibrated using experimental data. The results proved that the characterized model is capable of reproducing the mushrooming shape of the ductile fracture mode